Proposal for the Implementation of the Occupational Health and Safety Man-agement System in Compliance with Law 29783 to Prevent Workplace Acci-dents at EMIMSAC, 2024 (SCIÉNDO INGENIUM, 2026)
The management of Occupational Health and Safety (OHS) in Peru used to be limited; there was no preventive culture within companies. Workplace safety focused more on protecting machinery than on protecting workers, and safety largely depended on employees’ experience. Currently Occupational Health and Safety (OHS) has evolved in Peru, adopting a preventive, comprehensive, and participatory approach. With the enactment of Law 29783, the Occupational Health and Safety Law, all companies are required to implement an Occupational Health and Safety Management System (OHSMS), complemented by its regulation, Supreme Decree 005-2012-TR, and further detailed in Ministerial Resolution No. 050-2013-TR, which specifies the mandatory documents and records for its implementation. In the review of the system’s guidelines, the company EMIMSAC obtained a compliance score of 46.7%, receiving a “fair” rating. The PHVA (Plan–Do–Check–Act) method was applied, and two surveys related to accidents and safety were carried out. The company recorded six minor accidents during 2023, showing that the current system is insufficient to protect workers. The absence of an OHSMS exposes the company to potential fines and administrative sanctions by the National Superintendence of Labor Inspection (SUNAFIL). Based on the results obtained, the urgency of proposing the implementation of an OHS management system according to Law 29783 is justified.
Keywords: Prevention; Law 29783; occupational accidents